PERAN BI’AH LUGHAWIYAH DALAM MENGEMBANGKAN KEMAMPUAN FONOLOGIS MAHARAH ISTIMA’ SANTRI DI PONDOK PESANTREN AL-ITTIFAQIAH - Erma Sapitri; Novi Ulfa Safitri; Dini Kaspa; Baidinda Dwi Amanah (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
Many students at Islamic boarding schools face difficulties in distinguishing phonetically similar Arabic letters, such as ص and س, ذ and ز, as well as ض and ظ. These difficulties arise from phonological interference caused by regional languages that lack equivalent phonemes, which in turn hinders students’ maharah istima’ (Arabic listening skills). This situation highlights the need for a structured linguistic environment, or Bi’ah Lughawiyah, as a systematic solution. This study aims to: (1) describe the implementation of Bi’ah Lughawiyah at Al-Ittifaqiah Islamic Boarding School; (2) analyze its role in developing students’ phonological competence in maharah istima’; (3) identify phonological difficulties experienced by students in distinguishing Arabic phonemes; and (4) determine the supporting and inhibiting factors in students’ phonological development. This study employed a qualitative descriptive approach involving 30 students, 2 language supervisors, and 2 female teachers selected through purposive sampling. Data were collected through semi-structured interviews and observation, then analyzed using the Miles and Huberman interactive data analysis model, which consists of three stages: data reduction, data display, and conclusion drawing, with source triangulation. The results indicate that Bi’ah Lughawiyah positively impacts students’ phonological competence in maharah istima’: 26 out of 30 students reported improved listening ability, and 25 students stated that consistent exposure to Arabic speech helped them understand phoneme distinctions. Nevertheless, students still struggle to differentiate phonetically similar letters such as ص, س, ذ, ز, ض, and ظ due to phonological interference from regional languages. This study affirms that Bi’ah Lughawiyah functions not merely as a communication medium within the pesantren, but as an effective language acquisition instrument when implemented consistently and supported by all elements of the institution. ABSTRAK Banyak santri di pondok pesantren mengalami kesulitan dalam membedakan bunyi huruf hijaiyah yang mirip secara fonetis, seperti ص dengan س, ذ dengan ز, serta ض dengan ظ. Kesulitan ini muncul akibat interferensi fonologi dari bahasa daerah yang tidak mengenal fonem-fonem tersebut, sehingga kemampuan maharah istima’ santri pun terhambat. Kondisi ini mendorong perlunya lingkungan bahasa atau Bi’ah Lughawiyah yang terstruktur sebagai solusi. Penelitian ini bertujuan untuk: (1) mendeskripsikan penerapan Bi’ah Lughawiyah di Pondok Pesantren Al-Ittifaqiah; (2) menganalisis perannya dalam mengembangkan kemampuan fonologis maharah istima’ santri; (3) mengidentifikasi kesulitan fonologis santri dalam membedakan bunyi huruf hijaiyah; serta (4) menemukan faktor pendukung dan penghambat perkembangan fonologis tersebut. Penelitian menggunakan pendekatan kualitatif deskriptif dengan subjek 30 santri, 2 pengurus bahasa, dan 2 ustadzah yang dipilih secara purposive sampling. Data dikumpulkan melalui wawancara semi terstruktur dan observasi, kemudian dianalisis menggunakan model analisis data interaktif Miles dan Huberman yang mencakup tiga tahap: reduksi data, penyajian data, dan penarikan kesimpulan, dengan triangulasi sumber. Hasil menunjukkan bahwa Bi’ah Lughawiyah berdampak positif terhadap kemampuan fonologis maharah istima’ santri: 26 dari 30 santri merasakan peningkatan kemampuan menyimak, dan 25 santri menyatakan pembiasaan mendengar membantu pemahaman bunyi huruf. Namun, santri masih kesulitan membedakan huruf ص, س, ذ, ز, ض, dan ظ akibat interferensi fonologi bahasa daerah. Penelitian ini menegaskan bahwa Bi’ah Lughawiyah bukan sekadar media komunikasi pesantren, melainkan instrumen pemerolehan bahasa yang efektif apabila diterapkan secara konsisten dan didukung seluruh elemen pesantren.